Analisis Respons Dinamik Pelat Lantai Bangunan Ortotropik dengan Dua Pengaku yang Diberi Beban Ledakan - Meilani Meilani; Sofia W. Alisjahbana (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Bombings occurred in Indonesia mostly attack high-rise buildings. This fact should be a consideration for the structural engineer when designing high-rise building structures since the design of the structure does not include bomb blast burden in the calculation. This article discusses the dynamic response of buildings with of two plate stiffeners which are then given blast loads. The purpose of this study is to determine the effects of damping and the boom duration of the dynamic response of the plate. The plate is modeled damped orthotropic rectangular with semirigid placement on all sides. A decrease in plate element equilibrium equation is based on moment balance and forces on the plate. Meanwhile, the plate motion equations are derived using Newton's second law. The natural frequency of the plate system is obtained using the Modified Bolotin Method (MBM) as the numerical calculation process is completed with Microsoft Excel 2003 and Mathematica 5.2. Plates will be given damps as much as 0%, 5% and 10%. Each plate with each damp will be given blast loads for 1 ms, 2 ms, 10 ms and 20 ms. The research results shows that the greater the damp is used, the smaller system dynamic response will be. The longer the blast load works, the greater system dynamic response will be.